Are Universities Important for Explaining Unequal Participation in Student Mobility? A Comparison between Germany, Hungary, Italy and the UK - Sylke V. Schnepf; Elena Bastianelli; Zsuzsa Blaskó (Institute of Labor Economics (IZA), 2020)
Policies supporting international student mobility prepare young people for the challenges of global and multicultural environments. However, disadvantaged students have lower participation rates in mobility schemes, and hence benefit less from their positive impacts on career progression. Therefore, policy makers aim to make mobility programmes more inclusive. Nevertheless, it is far from clear how policy design can achieve this aim. This study investigates factors driving unequal mobility uptake. It goes beyond existing research by not only focusing on individual choices but also on university characteristics, like university segregation, excellence and student support. In addition, the study is novel in comparing rich graduate survey and administrative data merged with university level ETER data across four countries. Multilevel regression results show consistently across all countries that disadvantaged students do not only lose out on mobility experience due to their background but also due to them being clustered in universities with lower mobility opportunities. Universities' support and excellence while important for explaining mobility uptake do not appear to mitigate unequal uptake in any of the countries examined.
Keywords: I23; I24; D63; D02; 330; student support; segregation; inequality; unequal uptake; Erasmus+; international student mobility; university excellence; Germany; Hungary; Italy; UK